Influenza Vaccine Effectiveness among Elderly and Non-Elderly Adults Aged ≥45 Years in the United States, 2011–2012 to 2015–2016 - Havers, Fiona P (Open Forum Infect Dis, 2017)
BACKGROUND: While elderly adults have decreased immune responses to influenza vaccination compared with younger adults, few studies have compared influenza vaccine effectiveness among elderly and non-elderly adults. METHODS: We used data from the U.S. Influenza Vaccine Effectiveness (VE) Network over 5 influenza seasons from 2011–12 to 2015–16. We included data from adults aged ≥45 years seeking outpatient medical care for an acute respiratory illness within 7 days of illness onset. Combined nasal and oropharyngeal swabs were tested for influenza virus by RT-PCR. Current season vaccination was defined as receipt ≥14 days before illness onset of inactivated seasonal influenza vaccine (excluding high dose vaccine), according to medical records, immunization registries and self-report. VE was estimated as 100% x (1 – odds ratio) from multivariable logistic regression comparing odds of vaccination among influenza RT-PCR-positive vs. negative participants, controlling for age, comorbid conditions, illness duration, calendar time, race/ethnicity, sex, and study site. RESULTS: 10,640 adults aged ≥45 years were enrolled; 2592 (24%) tested influenza-positive, including 1993 (77%) influenza A (1268 [64%] A/H3N2 and 725 [36%] A/H1N1pdm09) and 551 (21%) influenza B viruses. Approximately 64% of adult patients had received current season vaccine; 57%, 76% and 83% among those aged 45–64, 65– 74 and ≥75 years, respectively. VE against outpatient influenza among patients aged ≥45 years ranged from 28% in 2014–15 to 55% in 2011–12, with an average of 42% (95% confidence interval [CI], 36–48) across five seasons. By virus (sub)type and age group, VE ranged from 5–36% against A/H3N2, 41–69% against A/H1N1pdm09, and 57–75% against influenza B (Table). CONCLUSION: Over 5 influenza seasons, influenza vaccine effectiveness against medically attended influenza did not differ significantly between elderly and non-elderly adults aged ≥45 years. Further investigation of the effect of medications and repeated vaccination are needed. DISCLOSURES: A. S. Monto, sanofi pasteur: Grant Investigator, Research grant; Novartis: Consultant, Consulting fee; Protein Sciences: Consultant, Consulting fee; E. T. Martin, Merck: Grant Investigator, Research grant; Roche: Grant Investigator, Research grant; E. A. Belongia, Medimmune: Investigator, Research grant; H. Q. McLean, MedImmune: Grant Investigator, Research support; M. Gaglani, MedImmune: Investigator, Research support; R. K. Zimmerman, Pfizer: Investigator, Research support; sanofi pasteur, Inc.: Investigator, Research support; Merck: Grant Investigator, Research grant; M. P. Nowalk, Merck: Grant Investigator, Research grant; L. A. Jackson, Novavax: Grant Investigator, Research grant